The Power Sector and its Impacts on Industrialization of Businesses in Nigeria - Amos, Akinbola Olufemi; Zekeri, Abu; Idowu, H. A. O. (Archives of Business Research, 2017)
The study investigates the link between power supply and business industrial development by examining the influence of government policies on power supply and industrial development in Nigeria. The Johansen Co-Integration technique was adopted to determine the long run relationship among some macroeconomic variables that includes the industrial component of Real Gross Domestic Product, explicitly chosen using explanatory variables. The independent variables includes electricity consumption, electricity production (Kwh), growth rate of labour force, real gross fixed capital formation and telephone lines per hundred population and their impact on industrial component of real GDP. Annual time series data on these variables from 1981 to 2010 were collected from the Central Bank of Nigeria Statistical Bulletin, the World Bank and United Nations Statistics. Augmented Dickey Fuller (ADF) and Phillip-Perron (PP) tests are employed to test the order of integration of the variables. The study also performed a Vector Error Correction Model-VECM to correct possible disequilibrium caused in the short-run relationships. The study concluded that electricity condition which is a result of existing government policies exerts a negative impact on industrial output in the long run affects the business viability.